Analisis Kesalahan Berbahasa Pada Surat Kabar Trinbun Batam: Analisis Kesalahan Berbahasa Pada Surat Kabar Trinbun Batam - Ng, Stanley; Yunisa Oktavia (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2021)
The problem in this study is an error in the Trinbun Batam newspaper in the form of errors in the use of words and errors in the use of punctuation. The object used in this study is the news contained in newspapers from Trinbun Batam on November 5, 2021 with newspaper number 51 Year XVII. The purpose of this study is to describe the language errors that exist in the Trinbun Batam newspaper in the form of errors in the use of words and errors in the use of punctuation marks; to provide corrections for errors in the use of punctuation marks and errors in the use of words and sentences. This type of research is a qualitative research which is this research is a research conducted by describing the data obtained using a series of sentences. The method used in this study is a method in which the data sources are obtained from words on the object of research in the form of newspapers and not in the form of numbers. The technique used in collecting data is to observe the object under study. In this study, it can be concluded that the language errors in the Trinbun Batam newspaper include: errors found in the news